Load-specific differences in the structure of femoral neck and tibia between world-class moguls skiers and slalom skiers - Nikander, R.; Sievänen, H.; Heinonen, A.; Karstila, T.; Kannus, P. (Scandinavian Journal of Medicine & Science in Sports, 2008)
Bone structure of weight-bearing proximal femur and tibia was examined among the Finnish world-class moguls skiers and slalom skiers. We hypothesized that these bones, during typical sport-specific performance, had been subjected not only to extreme loading but also to distinct loading in terms of rate and primary direction. Bone [dual-energy X-ray absorptiometry (DXA), peripheral quantitative computed tomography (pQCT), magnetic resonance imaging] and muscle performance data of the lower extremities were obtained from the five Finnish male moguls skiers and six slalom skiers competing at the World Cup level. Data (DXA, pQCT) from 12 age- and weight-matched normally active men were used for comparison. The ANCOVA with body height as a covariate was used for statistical analysis. The weight-bearing bones of the athletes were 10-60% stronger than those of the normally active men. Compared with the moguls skiers, the slalom skiers showed an average 43% thicker anterior cortex at the narrowest region of the femoral neck. This study suggests that the bone structure at skiers' heavily loaded lower extremities was very robust. A specific finding was the thick anterior cortex of the femoral neck among the slalom skiers. Apparently, the predominant loading type had modulated the site-specific skeletal response to physical exertion.